2016
DOI: 10.1007/s10557-016-6652-7
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Angiotensin-Converting Enzyme Inhibitors and Angiotensin-Receptor Blockers in Coronary Artery Disease without Heart Failure in the Modern Statin Era: a Meta-Analysis of Randomized-Controlled Trials

Abstract: In CAD patients without HF, ACEi, but not ARBs decreases the risk of non-fatal MI, cardiovascular mortality and all-cause mortality, while both ACEi and ARBs decrease the risk of stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…This suggests a protective effect of ACEI on myocardial systolic function. Previous metaanalyses have shown that ACEIs have multiple potential cardioprotective effects: controlling blood pressure and reducing LV hypertrophy as well as potentially exerting anti-atherosclerotic effects [26,27]. Furthermore, the mechanism of in uencing the coronary artery is an improvement in endotheliumdependent vasodilatation by increasing the level of bradykinin, increasing the expression and activity of nitric oxide synthase and reducing the production of smooth muscle proliferators [28].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a protective effect of ACEI on myocardial systolic function. Previous metaanalyses have shown that ACEIs have multiple potential cardioprotective effects: controlling blood pressure and reducing LV hypertrophy as well as potentially exerting anti-atherosclerotic effects [26,27]. Furthermore, the mechanism of in uencing the coronary artery is an improvement in endotheliumdependent vasodilatation by increasing the level of bradykinin, increasing the expression and activity of nitric oxide synthase and reducing the production of smooth muscle proliferators [28].…”
Section: Discussionmentioning
confidence: 99%
“…The cholesterol-independent or "pleiotropic" effects of statins include the upregulation and activation of endothelial NO synthase, especially in the presence of hypoxia [22,23]. One meta-analysis study [24] demonstrated that the percentage of patients on statin therapy showed no significant relationship with the reduction in outcomes due to ACEI. In addition, in the ARB trials, no statistical significance was found in terms of outcome and percentage of patients on statin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Hoang et al performed a meta-analysis based on randomized control trials to investigate the effects of statin use combined with use of ACEIs and ARBs on cardiovascular disease prevention. They noted that the effect of ACEIs/ARBs in reducing cardiovascular morality was attenuated after adjusting for statin use [ 1 ]. This finding supports that the combined use of statins and ACEIs/ARBs might have interactions that cannot be neglected in reducing pneumonia, which needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin-converting enzyme inhibitors (ACEIs) / Angiotensin receptor blockers (ARBs) and statins are widely used to treat patients with cardiovascular diseases to modify primary and secondary risks. These medications have demonstrated beneficial effects in improving outcomes in patients with cardiovascular diseases [ 1 , 2 ]. Hypertension and hyperlipidemia are prevalent among cardiovascular patients; therefore, the combined use of these two kinds of medications is not uncommon in clinical scenarios.…”
Section: Introductionmentioning
confidence: 99%